2001
DOI: 10.1002/1527-2648(200107)3:7<475::aid-adem475>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Iron Filamentary Microcomposites

Abstract: The Cu–Fe system is of particular interest because of the relatively low cost of Fe compared to other insoluble BCC phases such as Nb, Mo, Cr, and Ta. The relatively high solubility of Fe in Cu at high temperatures, coupled with the slow kinetics of Fe precipitation at low temperatures is, however, known to reduce electrical conductivity. The key to improving strength/conductivity properties is to reduce the initial dendrite size and to precipitate Fe effectively in the Cu matrix. Thermomechanical treatments h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 12 publications
0
38
2
Order By: Relevance
“…Iwahashi et al [19] studied the effect of processing parameters on the grain refinement in Al and found that the subgrain and grain size are in the range of 0.5 µm to 1.5 µm. The microstructural scale of deformation-processed Cu base composites treated by rolling and drawing was found to be much smaller at high deformation strains [1][2][3][4][5][6][7][8][9][10][11]. For example, in Cu-Nb nanocomposites processed by drawing, the spacing between the Nb filaments or the subgrain size in the Cu matrix was approximately 100 nm, while the thickness of the Nb filaments was as thin as 13 nm at the estimated drawing strain of 8.5 [8,11].…”
Section: Introductioncontrasting
confidence: 63%
See 4 more Smart Citations
“…Iwahashi et al [19] studied the effect of processing parameters on the grain refinement in Al and found that the subgrain and grain size are in the range of 0.5 µm to 1.5 µm. The microstructural scale of deformation-processed Cu base composites treated by rolling and drawing was found to be much smaller at high deformation strains [1][2][3][4][5][6][7][8][9][10][11]. For example, in Cu-Nb nanocomposites processed by drawing, the spacing between the Nb filaments or the subgrain size in the Cu matrix was approximately 100 nm, while the thickness of the Nb filaments was as thin as 13 nm at the estimated drawing strain of 8.5 [8,11].…”
Section: Introductioncontrasting
confidence: 63%
“…The microstructural development and strengthening mechanism of deformation-processed Cu base microcomposites have been the subjects of extensive studies [1][2][3][4][5][6][7][8][9][10][11]. Deformation processing methods such as drawing or rolling have been employed in such research to refine the microstructure, leading to a fine two-phase microstructure with strong crystallographic textures [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations